Ayurvedic Management of Putraghani Yonivyapada (Recurrent Abortions): A Case Report - Lata Rai; Uttara Kumar Chaturvedi; Poonam Choudhary; K.Bharathi (International Journal of Ayurveda and Pharma Research, 2022)
Recurrent miscarriages are characterized as three or more spontaneous abortions in a row before the 20th week. In the majority of instances, genetic factors, immunological and endocrine factors, infection, and unknown causes are the most common causes of first trimester abortion. Hormonal therapy, heparin injection, and immunotherapy are the available treatments. In this case study, the patient had three abortions during the first trimester. Because all of the tests came out normal, the diagnosis of unexplained recurrent abortions was made. For 40 days before conception, the patient was treated with Ayurvedic medications such as Indukanta Ghrita, Phalghrita. The patient was conceived with these drugs, and later Phalaghrita and other medicines were given for the duration of the pregnancy. Ayurvedic medicine is an effective way to deal with recurring abortions.